The Association Between Social Support, Violence, and Social Service Needs Among a Select Sample of Urban Adults in Baltimore City - Chandran, Aruna; Long, Amanda; Price, Ashley; Murray, Jeannie; Fields, Errol L.; Schumacher, Christina M.; Greenbaum, Adena; Jennings, Jacky M. (Journal of community health, 2020)
Experiencing violence has been associated with negative health outcomes. The objectives of this study were to determine whether experiencing violence is associated increased support service needs and suboptimal general health indicators. In addition, we explore the relationship between these and perceived social support among a select sample of urban predominantly male adults in Baltimore City. A cross-sectional survey was conducted among 187 adults being seen in one of seven urban partner agencies participating in a parent HIV prevention and treatment demonstration project. Associations were examined using a multivariable logistic regression model, adjusting for the clinic site at which the client was being seen as well as age and gender identity. There was a significant amount of violence experienced by this population; 131 (72%) reported having seen someone be physically assaulted, and 89 (49%) had been physically assaulted without a weapon. Direct victimization from violence was associated with a threefold increased odds of needing housing and mental health/substance use services. Exposure to violence was associated with a threefold increase in needing housing and mental health/substance use services, and with sub-optimal health status. Perceived social support was associated with 30% decreased reports of experiencing violence. In conclusion, our select sample of urban adults report having experienced high rates of violence, and this is associated with increased support service needs as well as suboptimal perceived health status. Incorporating care for the effects of experiencing violence as well as social service needs are important in optimizing the health of urban populations.